Socialization During the COVID-19 Pandemic: The Role of Social and Scientific Networks During Social Distancing - AYDINER, ELİF (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
In the COVID-19 era, while we are encouraged to be physically far away from each other, social and scientific networking is needed more than ever. The dire consequences of social distancing can be diminished by social networking. Social media, a quintessential component of social networking, facilitates the dissemination of reliable information and fighting against misinformation by health authorities. Distance learning, telemedicine, and telehealth are among the most prominent applications of networking during this pandemic. Additionally, the COVID-19 pandemic highlights the importance of collaborative scientific efforts. In this chapter, we summarize the advantages of harnessing both social and scientific networking in minimizing the harms of this pandemic. We also discuss the extra collaborative measures we can take in our fight against COVID-19, particularly in the scientific field.
Keywords: COVID-19; Pandemic; Scientific network; Social distancing; Social network; Socialization